Rovibrational laser control targeting a dark state in acetylene. Simulation in the Ns = 1, Nr = 5 polyad. (2nd September 2018) - Santos, L.; Herman, M.; Desouter-Lecomte, M.; Vaeck, N.
ABSTRACT: Optimal control theory in the Liouville space is used to perform rovibrational control by means of a laser pulse in a polyad of acetylene in order to populate a dark vibrational state. The initial mixed state is a truncated Boltzmann distribution of rotational levels from J =27 to J =31 of the ground vibrational state. The target state is a rotational equidistribution of levels ranging from J =28 to J =32 of the first excited vibrational dark state including quanta of energy in each bending modes, with positive vibrational angular momenta. The simulation is performed by using a manifold of eigenstates of a full-dimensional Hamiltonian calibrated by high precision spectroscopy known as the global acetylene Hamiltonian [B. Amyay et al., J. Chem. Phys.131, 114301 (2009)]. The control is successful as an Uhlmann's fidelity of 0.98 is reached. GRAPHICAL ABSTRACT: